An Implicit Function Implies Several Contraction Conditions - Ali, Javid; Imdad, M. (Sarajevo Journal of Mathematics, 2024)
In this paper, we define a new implicit function which includes a majority of contractions of the existing literature of metric fixed point theory and then utilize the same to prove a general common fixed point theorem for two pairs of weakly compatible mappings satisfying the common property (E.A). In the process, a host of previously known results are improved and generalized. Some related results are derived besides furnishing illustrative examples. 2000 Mathematics Subject Classification. 47H10, 54H25